Numerical analysis of heat transfer due to slot jets impingement onto two cylinders with different diameters - Varol, Yasin; Alnak, Dogan E.; Öztop, Hakan Fehmi; Al-Salem, Khaled (Pergamon-Elsevier Science Ltd, 2012)
A numerical investigation has been performed two-dimensional slot impingement onto two heated cylinders with different diameters turbulent flow conditions. Height of slot jet is taken as constant for all cases. The study is performed to see the effects of effective parameters on heat and fluid flow as jet Reynolds number (11,000 <= Re <= 20,000), diameter ratio of cylinders (0.5 <= D-1/D-2 <= 1.5) and ratio of distance between cylinders to slot jet high (L/S). Streamlines, isotherms, local and mean Nusselt numbers and Cd coefficient were obtained. These results were compared with earlier experimental and numerical works and good agreement was obtained. It is found that diameter ratios of cylinders can be a control element for heat and fluid flow. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Jet impingement; Turbulent flow; Heat transfer; Cooling